Combination of Woolwich massage and hydrogel made from red ginger for breastfeeding mothers to increase baby weight - Khaeriyah, Hana Nurul; Sudirman, Sudirman; Hendriyani, Heni (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2023)
Background: The amount of breast milk that nursing moms make is still insufficient, affecting the infant's weight. One attempt to increase the baby's weight is administering a combination of Woolwich massage and red ginger hydrogel, which has never been done in prior studies. Purpose: To demonstrate the impact of a Woolwich massage and red ginger hydrogel on infant weight. Method: This experimental study with a pre-post-test control group design. Thirty-six breastfeeding mother respondents were selected using simple random sampling; 18 were given a combination of Woolwich massage and red ginger hydrogel, and 18 were given standard breast care during the postpartum period. Treatment was given for seven days—analysis of baby weight using the Paired Samples T-Test and the Mann-Whitney test. Results: The average increase in body weight of infants of the intervention group (405,56 g) was higher than the control group (238,89 g), p<0.05. Conclusion: Breastfeeding mothers given a combination of Woolwich massage and hydrogel made from red ginger rhizomes could have babies with a higher birth weight than mothers who were only given standard breast care.